Treatment of the Nasolabial Fold Using a Hyaluronic Acid-Based Filler with eXcellent Three-Dimensional Reticulation (XTR™) Technology: A Retrospective Study - Abdulbaky AHI; Wong V (Dove Medical Press, 2024)
Abdulrahman Hassan Imam Abdulbaky, Vincent Wong TriVin Aesthetics, London, UKCorrespondence: Vincent Wong, TriVin Aesthetics, 10 Harley Street, London, W1G 9PF, UK, Tel +44 207 299 0380, Fax +44 207 467 8312, Email info@drvincentwong.comPurpose: The physicochemical characteristics of hyaluronic acid (HA) fillers can affect the outcome of minimally invasive aesthetic treatments. The effect of a novel HA-based filler manufactured with a novel 3D structure (XTRTM technology) was assessed in the nasolabial fold.Patients and Methods: We performed a retrospective study of patients who underwent treatment of the nasolabial fold with a novel HA filler in our clinic. Treatment outcome was assessed at 3 and 6 months with wrinkle score, GAIS, and VAS.Results: Eighteen patients were injected with the novel HA filler in the nasolabial fold. At six months, mean wrinkle scores were improved on both sides compared to baseline. GAIS and VAS were high at three and six months.Conclusion: The HA-based filler manufactured with XTRTM technology is safe and effective in treating the nasolabial fold. Good aesthetic results were seen for up to 6 months. Patient satisfaction was high during the entire follow-up.Keywords: filler injection, face rejuvenation, monophasic, crosslinking technology